Age Cohort Differences in Sexual Behaviors Among Black Men Who Have Sex With Men and Women. Issue 8 (13th October 2018) - Dangerfield, Derek T.; Harawa, Nina T.; Fernandez, M. Isabel; Hosek, Sybil; Lauby, Jennifer; Joseph, Heather; Frank, Heather Guentzel; Bluthenthal, Ricky N.
Abstract : Little attention has focused on generational or age-related differences in human immunodeficiency virus/sexually transmitted infection (HIV/STI) risk behaviors among Black men who have sex with men and women (BMSMW). We examined sexual risk behaviors between BMSMW ages 40 and under compared to over age 40. Analysis was conducted using Centers for Disease Control and Prevention (CDC)–sponsored intervention data among BMSMW in Los Angeles, Chicago, and Philadelphia ( n = 546). Pearson's chi-square tests were conducted to evaluate associations between age groups and behavioral outcomes. Logistic regression was used to evaluate the odds of behavioral outcomes by age group, adjusting for sexual orientation and study location, within strata of HIV status. HIV-positive BMSMW over age 40 had 62% reduced odds of having a nonmain female partner of HIV-negative or unknown status compared to those ages 40 and under (adjusted odds ratio [AOR] 0.38, 95% confidence interval [CI] = 0.15, 0.95). Among HIV-negative BMSMW, the older cohort was associated with greater odds of having condomless insertive anal intercourse (IAI) with most recent main male partner (AOR 2.44, 95% CI = 1.12, 5.32) and having a concurrent partnership while with their recent main female partner (AOR = 2.6, 95% CI = 1.10, 4.67). For both groups, odds of engaging in certain risk behaviors increased with increasing age. Prevention efforts should consider generational differences and age in HIV risks among BMSMW.